2009
DOI: 10.1029/2009gl040598
|View full text |Cite
|
Sign up to set email alerts
|

On the recent warming in the Murray‐Darling Basin: Land surface interactions misunderstood

Abstract: [1] Previous studies of the recent drought in the MurrayDarling Basin (MDB) have noted that low rainfall totals have been accompanied by anomalously high air temperatures. Subsequent studies have interpreted an identified trend in the residual timeseries of non-rainfall related temperature variability as a signal of anthropogenic change, further speculating that increased air temperature has exacerbated the drought through increasing evapotranspiration rates. In this study, we explore an alternative explanatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…CSIRO, 2008), increasing irrigation and/or farm dam extractions (e.g. CSIRO, 2008), increased air pollution (Rosenfeld, 2000), increased sunshine hours (Lockart et al, 2009) and, of specific interest for this study, changes in the seasonality of rainfall -in particular, changes in the way seasonal totals are compiled (i.e. changes to the frequency, intensity, duration and/or sequencing of rainfall events).…”
Section: Hydrological Implications Of the Post-1994 Change In Rainfalmentioning
confidence: 99%
“…CSIRO, 2008), increasing irrigation and/or farm dam extractions (e.g. CSIRO, 2008), increased air pollution (Rosenfeld, 2000), increased sunshine hours (Lockart et al, 2009) and, of specific interest for this study, changes in the seasonality of rainfall -in particular, changes in the way seasonal totals are compiled (i.e. changes to the frequency, intensity, duration and/or sequencing of rainfall events).…”
Section: Hydrological Implications Of the Post-1994 Change In Rainfalmentioning
confidence: 99%
“…Rising temperatures may have been a factor as has been suggested for eastern Australia over recent time (Nicholls, 2004;Cai et al, 2009). However, both observational evidence (Roderick et al, 2009) and theoretical arguments (Lockart et al, 2009), suggest that temperature is not a strong driver of evaporation. Bates et al (2010) concluded that the decline in annual inflows was consistent with a decline in average rainfall accompanied by decreases both in the frequency of daily precipitation occurrence and in wet day amounts.…”
Section: Introductionmentioning
confidence: 96%
“…We agree that the averaging procedure used in LKF was not adjusted for latitude‐dependency in the climatology. Such limitations of the MDB‐averaged time series were explicitly acknowledged in our paper [ Lockart et al ., 2009, p. 2] with regard to the potential for spuriously improved correlation to Tmax, but not in the context of any potential trend in the residual time series. It is this omission that generated the comment by CCBJR.…”
mentioning
confidence: 91%